Tourette Syndrome, Motor Cortex Excitability and Comorbidity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
Motor cortex excitability in 29 untreated adult Gilles de la Tourette syndrome (TS) patients was measured using transcranial magnetic stimulation in a study at the Institute of Neurology, London, UK, and University of Ulm, Germany.